1. Solve one of the equations for one variable in terms of the other variable.
2. Substitute the expression for that variable into the other equation.
3. Solve the resulting equation for the remaining variable.
4. Substitute the value found for the remaining variable back into the expression for the other variable to find its value.
5. Check the solution by substituting the values found for both variables into the original equations to see if they are true.
Put the steps in order that are used to solve the following systems of equations by substitution.
−7x−2y=−13 and x−2y=11
x-2y=11--> x=2y+11
-7(2y+11)-2y=13
-16y=64,(3,-4)
x=3, x-2(-4)=11
-16-77=-13
y=-4
x+8=11
-14y-77-2y=-13
3 answers
ni its 8 steps
Apologies for the confusion. Here are the correct steps:
1. Solve one of the equations for one variable in terms of the other variable. Let's solve the second equation for x: x = 2y + 11.
2. Substitute the expression x = 2y + 11 into the other equation. We get: -7(2y + 11) - 2y = -13.
3. Distribute -7 to 2y and 11: -14y - 77 - 2y = -13.
4. Combine like terms: -16y - 77 = -13.
5. Add 77 to both sides: -16y = 64.
6. Divide both sides by -16: y = -4.
7. Substitute the value of y = -4 back into the expression for x: x = 2(-4) + 11 = 3.
8. Check the solution by substituting the values of x = 3 and y = -4 into both original equations to see if they are true. The equations are satisfied, so the solution is correct: -7(3) - 2(-4) = -13 and 3 - 2(-4) = 11.
1. Solve one of the equations for one variable in terms of the other variable. Let's solve the second equation for x: x = 2y + 11.
2. Substitute the expression x = 2y + 11 into the other equation. We get: -7(2y + 11) - 2y = -13.
3. Distribute -7 to 2y and 11: -14y - 77 - 2y = -13.
4. Combine like terms: -16y - 77 = -13.
5. Add 77 to both sides: -16y = 64.
6. Divide both sides by -16: y = -4.
7. Substitute the value of y = -4 back into the expression for x: x = 2(-4) + 11 = 3.
8. Check the solution by substituting the values of x = 3 and y = -4 into both original equations to see if they are true. The equations are satisfied, so the solution is correct: -7(3) - 2(-4) = -13 and 3 - 2(-4) = 11.